2019
DOI: 10.1002/chem.201902150
|View full text |Cite
|
Sign up to set email alerts
|

Arylazo‐3,5‐dimethylisoxazoles: Azoheteroarene Photoswitches Exhibiting High Z‐Isomer Stability, Solid‐State Photochromism, and Reversible Light‐Induced Phase Transition

Abstract: Reversibly photoswitchable phenylazo‐3,5‐dimethylisoxazole and 37 aryl‐substituted derivatives were synthesized. Excellent photoswitching ability of these compounds in solution and the solid state was demonstrated. Through kinetics studies by means of NMR spectroscopy, high Z‐isomer stability was demonstrated. Interestingly, the majority of the derivatives showed light‐induced contrasting color changes in solution and the solid state. Besides, many of the derivatives exhibit partial phase transition upon UV ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 45 publications
3
74
1
2
Order By: Relevance
“…Owing to mesomerism, 46 the uncatalysed half-life of the 4alkoxy-substituted Z-AIZs 2 and 3 in solution was determined to be 7 d 44 rather than the 45 d for Z-AIZ 1. 43 Although we observe no reactivity of Z-AIZ 2 and 3 to a large excess of acetic acid (CH3COOH, 5000 equivalents in acetonitrile, Figure S8), addition of CF3COOH and HCl cause the half-life to diminish to the (sub)second timescale at near-stoichiometric amounts already (Figure S9 and S10). DFT calculations of activation free energies confirm that the Zto E-barrier is substantially reduced in the azonium species from 1.29 eV (versus 1.11 eV experimentally 44 ) to 0.86 eV (Figure 2A).…”
Section: Accelerated Z-to E-reversion With Weak Acidsmentioning
confidence: 83%
“…Owing to mesomerism, 46 the uncatalysed half-life of the 4alkoxy-substituted Z-AIZs 2 and 3 in solution was determined to be 7 d 44 rather than the 45 d for Z-AIZ 1. 43 Although we observe no reactivity of Z-AIZ 2 and 3 to a large excess of acetic acid (CH3COOH, 5000 equivalents in acetonitrile, Figure S8), addition of CF3COOH and HCl cause the half-life to diminish to the (sub)second timescale at near-stoichiometric amounts already (Figure S9 and S10). DFT calculations of activation free energies confirm that the Zto E-barrier is substantially reduced in the azonium species from 1.29 eV (versus 1.11 eV experimentally 44 ) to 0.86 eV (Figure 2A).…”
Section: Accelerated Z-to E-reversion With Weak Acidsmentioning
confidence: 83%
“…For accessing the amide derivatives 1 a – c and 2 a – c , their corresponding amino azobenzenes ( 11 a – c ) or the N ‐methylated aminoazobenzene analogs ( 12 a – c ) have been treated with the in situ generated trimesoylchloride 10 , derived from trimesic acid 9 [3c, 10, 15] . In a similar procedure, 3 a – c and 4 a – c have been synthesized using the corresponding amine derivatives or their N ‐methylated analogs of phenylazo‐3,5‐dimethylisoxazoles ( 13 a – c and 14 a – c ) [6b, 14c] . For the synthesis of triazine derivatives 5 a – c , aromatic nucleophilic substitution has been exploited using the corresponding aminoazobenzene derivatives 11 a – c and cyanuric chloride 16 [16] .…”
Section: Resultsmentioning
confidence: 99%
“…[10] Thediversity of heterocycles and their distinct nature from benzene provide tremendous opportunities to regulate the performance of azo switches.Six-membered rings such as pyridine [11] and pyrimidine [12] afforded heteroaryl azo switches in which coordination interactions and hydrogen bonding could be utilized. Significantly,mono-heteroaryl azo molecules (Ph-N=N-Het) based on five-membered rings (imidazole, [13] pyrazole, [14] pyrrole, [14] thiophene, [15] isoxazole, [16] etc.) showed some unusual features.Herges group [13b] and Fuchter group [14a] reported that Z-isomers of phenylazoimidazoles and phenylazopyrazoles could adopt aTshaped geometry (where the phenyl ring was orthogonal to the azo-heterocycle moiety) not accessible by azobenzenes.…”
Section: Introductionmentioning
confidence: 99%